Erratum: Alnowibet et al. Healthcare Human Resources: Trends and Demand in Saudi Arabia. Healthcare 2021, 9, 955 - Khalid Alnowibet (MDPI AG, 2021)
Some details of the authors’ names, affiliations, and email addresses were incorrect in the original version of the article [...]